2016
DOI: 10.1111/ede.12175
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in sister species of Leucoraja skate and its relationship to reproductive strategy and life history

Abstract: Instances of sexual dimorphism occur in a great variety of forms and manifestations. Most skates (Batoidea: Rajoidei) display some level of body shape dimorphism in which the pectoral fins of mature males develop to create a distinct bell-shaped body not found in females. This particular form of dimorphism is present in each of the sister species Leucoraja erinacea and Leucoraja ocellata, but differences between sexes are much greater in the former. In order to understand the nature and potential causes of pec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
0
6
2
Order By: Relevance
“…The display of long-distance dispersal capabilities in Winter Skate individuals prompts questions regarding the current understanding of their population dynamics, which suggested that individuals do not make long-distance migrations and exhibit high endemicity to specific regions of the continental shelf (Kulka et al 2009). Additionally, while we did not observe compelling evidence of differences in mobility between male and female Winter Skate, the presence of sexually dimorphic pectoral fin shapes in this species (Martinez et al 2016b) suggests that further work is needed to confirm whether more fine-scale or subtle patterns of spatial differentiation exist.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…The display of long-distance dispersal capabilities in Winter Skate individuals prompts questions regarding the current understanding of their population dynamics, which suggested that individuals do not make long-distance migrations and exhibit high endemicity to specific regions of the continental shelf (Kulka et al 2009). Additionally, while we did not observe compelling evidence of differences in mobility between male and female Winter Skate, the presence of sexually dimorphic pectoral fin shapes in this species (Martinez et al 2016b) suggests that further work is needed to confirm whether more fine-scale or subtle patterns of spatial differentiation exist.…”
Section: Discussioncontrasting
confidence: 77%
“…Additionally, while we did not observe compelling evidence of differences in mobility between male and female Winter Skate, the presence of sexually dimorphic pectoral fin shapes in this species (Martinez et al. ) suggests that further work is needed to confirm whether more fine‐scale or subtle patterns of spatial differentiation exist.…”
Section: Discussioncontrasting
confidence: 65%
“…Effort was made to primarily include adult specimens, but in some instances (e.g., very large species) smaller individuals were used. We used both male and female individuals, although sexual dimorphism does occur in some batoid species (e.g., Martinez et al, ). However, inspection of the major axes of variation did not indicate that sex influenced overall interpretations.…”
Section: Methodsmentioning
confidence: 99%
“…Sexual dimorphism in W D may occur in species with sexual differences in length‐width relationships (Ebert et al, ) and has been observed in other rajoids (Oddone & Vooren, ; Orlov & Cotton, ). Such dimorphism may be related to the onset of maturity, since it becomes evident in developing and adult individuals (Martinez et al, ).…”
Section: Discussionmentioning
confidence: 99%